Empirical Investigation on Factors Related to Individual of Impact Performance Information System - Tri Lathif Mardi Suryanto; Djoko Budiyanto Setyohadi; Nur Cahyo Wibowo (IAES Indonesia Section, 2017)
Today, many Information System Success studies are performed however only a few studies which focused on the impact of a personal user to succeed of applying IS. The aim of this study is to investigate and to measure the effect of End User Computing Satisfaction into Individual of Impact Performance, with regard the successful implementation of Information system at higher education. Random sampling technique is conducted offline on 100 IS college users and Structural Equation Model technique is used to analyze survey data based on Information System Success model. Our result show that IOIP is influenced by EUCS.